Industrial and process furnaces : principles, design and operation - Mullinger, Peter (Engineering professional collection, 2013)
This book contains up-to-date and comprehensive reference encompassing not only best practice of operation but the essential elements of furnace theory and design, essential to anyone working with furnaces, ovens and combustion-based systems.